До історії вивчення однієї теракоти з Ольвії - Русяєва, А.С. (Археологія, 2016)
Наведено окремі доповнення та авторські спостереження і пояснення до нового вивчення ольвійської теракоти. On the 100th anniversary of A.I. Furmanska, the authorship of the protome’s discovery during her excavations at the Olbian necropolis in 1956 is resumed. The protome was recently restored and comprehensively discussed in the publication by A.S. Borysiuk-Dudkina and T.M. Shevchenko. In this article, presented are various additions to its study, analogies, judgements allowing the author to interpret the depiction on protome as Demeter with a ritual gesture peculiar for her, according to A.I. Furmanska. However, the determination of more or less exact prototype of protome, of the absolute dating, and of precise place of production remains to be problematic. Nevertheless, in objective solving of these problems, it is important to visually compare the protome with numerous protomai of this type produced in Bosporus in the Early Hellenistic period. По случаю столетия со дня рождения А.И. Фурманской проведено восстановление авторства находки протомы во время ее раскопок ольвийского некрополя в 1956 г. Недавно она была реставрирована и в полном объеме рассмотрена в публикации А.С. Борисюк-Дудкиной и Т.М. Шевченко. В данной статье представлены различные дополнения к ее изучению, аналогии, суждения, которые дают возможность интерпретировать изображение на протоме как Деметру с характерным для нее ритуальным жестом, согласно с А.И. Фурманской. Проблематичным однако остается определение более-менее точного прототипа протомы, абсолютной датировки и конкретного места изготовления. Тем не менее, при объективном решении этих вопросов исключительно важное значение принадлежит визуальному ее сопоставлению с многочисленными протомами этого типа боспорского производства раннеэллинистического периода.